Dinamika populasi wereng punggung putih, sogatella furcifera Stal (Hemiptera: Delphacidae) di jawa tengah - Widiarta, I Nyoman; Wijay, E.S.; Sawada, Hiroichi (Perhimpunan Entomologi Indonesia, 2006)
A field study was conducted at paddy fields in Petarukan and Pekalongan regencies of Central Java province during wet season crop 1989/90 and 1990/91 to elucidate population dynamic of whitebacked planthopper, Sogatella furcifera Stí¥l. Seven and three observation fields were set up in 1989/90 and the 1990/91, respectively. Cisadane rice cultivar was transplanted following the usual farmer's parctices except that no pesticide was applied. The population of the whitebacked planthopper and the brown planthopper, (Nilaparvata lugens Stí¥l) were sampled by using an insect suction catcher, a farmcop. Identification of generation was based on thermal constant required by the whitebacked planthopper to complete one generation and mean population density was calculated by graphical method. Two distinct seasonal population growth patterns were identified. The population with short population growth pattern completed four generations in one crop season in which their population density increased consecutively in two generations since immigrant generation, and thereafter decreased. The population with long population growth completed five generations in one crop season in which their population density increased consecutively in three generations, and thereafter decreased. The density of brachiptera adults determined 90% of the total population density. The proportion of brachiptera adults were not correlated with large nymphal density in both vegetative and generative stages of rice. The proportion of brachiptera adults showed significant negative linear regression with population density of the brown planthopper. Therefore, interspesific competition determined the proportion of wingform and population dynamics of the whitebacked planthopper.